Come forth : the promise of Jesus's greatest miracle - Martin, James, 1960- (Harper One, an imprint of HarperCollinsPublishers, 2023)
"In this wise and compassionate book, New York Times bestselling author Father James Martin, SJ, explores the story of Jesus's greatest miracle-the raising of Lazarus from the dead-and what Jesus means when he calls each of us to "come forth." Meditatively and carefully, Father Martin leads us verse by verse, offering profound reflections on Jesus's lessons on love, family, sadness, frustration, fear, anger, freedom, and joy. Come Forth combines compelling analysis of the biblical text, insights about the historical setting of the story, spiritual lessons for today's readers, meditations on Lazarus in art and the larger culture, as well as stories from Martin's travels through the Holy Land. As he explores these strands in depth, Martin helps us let go of the limiting beliefs that prevent us from experiencing God's presence in our lives. We need only to open ourselves to the transformative story of Lazarus and trust that God can use it to free us to experience, like Lazarus, new life"--